KAJIAN METODE GRUP INVESTIGATION PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Boby Hendro Wardono (CV. Adiba Aisha Amira, 2023)
The aim of this research is to determine the implementation of the group investigation method in the process of learning Islamic Religious Education. This study is conducted using a literature review method, which involves reviewing and analyzing the research results that have been previously conducted. The articles and books used in this study cover the last 13 years, from 2010 to 2023. The data search and collection were carried out by exploring e-journals using Google Scholar. The research findings indicate that the learning process of Islamic Religious Education can be carried out using the group investigation method, which involves five stages: planning, implementation, analysis and synthesis, presentation of results, and the final stage, evaluation.